Identification of coexisting Mfrprd6 and Pde6brd10 mutations causing spontaneous retinal detachment in commercially available rd6 mice - Asaka Lee Shiozawa; Maika Hosoi Kobayashi; Yusuke Shiozawa; Yasuhiro Ikeda; Yoshitaka Miyagawa; Fumiki Okamoto; Mashito Sakai; Takashi Okada; Tsutomu Igarashi (PLoS ONE, 2025)
Purpose The rd6 mouse model, characterized by retinal degeneration due to an Mfrp mutation, has been widely studied. However, we identified a subset of rd6 mice that developed severe non-rhegmatogenous retinal detachment (rd6-RD), suggesting the presence of additional genetic factors. This study aimed to characterize the retinal phenotype of rd6-RD mice and identify potential causative genetic mutations. Methods We performed optical coherence tomography, fundus imaging, electroretinography, and histological analysis to compare retinal structures and functions between rd6, rd6-RD, and C57BL/6J mice. Whole-genome sequencing was conducted to identify potential mutations associated with the retinal detachment phenotype. Results Optical coherence tomography revealed retinal detachment in rd6-RD mice as early as 4 weeks old, with complete loss of the outer nuclear layer by 6 weeks. Fundus examination at 11 weeks showed pale fundi and narrowed, whitened retinal vessels in rd6-RD mice, distinct from rd6 mice. On electroretinography, rd6-RD mice displayed significantly diminished a- and b-wave amplitudes, with no detectable responses by 10 weeks. Histological analysis confirmed severe outer retinal degeneration and disappearance of the outer layers in rd6-RD mice. Whole-genome sequencing identified a missense R560C mutation in Pde6b, corresponding to the Pde6brd10 mutation, in rd6-RD mice. Conclusions A subset of rd6 mice exhibited severe retinal detachment and outer retinal degeneration, distinct from the previously characterized Mfrp-related phenotype. The identification of the Pde6brd10 mutation suggests that these mice possess a dual-mutant genotype (Mfrprd6 and Pde6brd10), exacerbating retinal degeneration. These findings highlight the importance of genetic verification in commercially available mouse models and provide new insights into the genetic complexity of inherited retinal degenerations.